1994
DOI: 10.1126/science.8047885
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of RNA Polymerase II Elongation by Chromosomal Protein HMG-14

Abstract: The high-mobility group protein 14 (HMG-14) is a non-histone chromosomal protein that is preferentially associated with transcriptionally active chromatin. To assess the effect of HMG-14 on transcription by RNA polymerase II, in vivo-assembled chromatin with elevated amounts of HMG-14 was obtained. Here it is shown that HMG-14 enhanced transcription on chromatin templates but not on DNA templates. This protein stimulated the rate of elongation by RNA polymerase II but not the level of initiation of transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 27 publications
6
60
1
Order By: Relevance
“…Early studies suggested that the chromatin of actively transcribed globin gene is depleted of H1 and enriched in HMGNs (50). Likewise, in an in vitro chromatin assembly system HMGN1 alleviates H1-mediated inhibition of transcription from SV40 promoters (29). These findings correlate well with more recent findings indicating that in living cells HMGN proteins compete with H1 for chromatin binding sites (43).…”
Section: Comparison With Hmgn1supporting
confidence: 81%
“…Early studies suggested that the chromatin of actively transcribed globin gene is depleted of H1 and enriched in HMGNs (50). Likewise, in an in vitro chromatin assembly system HMGN1 alleviates H1-mediated inhibition of transcription from SV40 promoters (29). These findings correlate well with more recent findings indicating that in living cells HMGN proteins compete with H1 for chromatin binding sites (43).…”
Section: Comparison With Hmgn1supporting
confidence: 81%
“…For example, nucleosomes have been described to impede transcriptional elongation (Izban and Luse 1991). Recently, HMG-14, a nonhistone chromosomal protein, has been reported to increase transcriptional elongation about fourfold in in vitro transcription reactions on nucleosomal templates (Ding et al 1994). Although HMG-14 and other nonhistone proteins are abundant nuclear proteins, some are found only in transcriptionally active regions {Weisbrod et al 1980).…”
Section: Elongation Rate As An Important Mechanism For Gene Regulationmentioning
confidence: 99%
“…Thus, most likely the behavioral changes seen in mice with altered HMGN1 expression are not solely due to its effect on MeCP2 levels but rather to the global effect due to HMGN1 impact on gene expression. Indeed, in vitro chromatin studies indicated that HMGN1 affects the rate of transcription (5,13), and recent studies revealed that either up-or down-regulation of HMGN1 levels affect the expression of numerous genes, albeit most of the changes were relatively small (14).…”
Section: Hmgn1mentioning
confidence: 99%
“…The interaction of HMGN1 with nucleosomes, which is highly dynamic (7)(8)(9), modulates the structure of chromatin (5,6) and the levels of histone modifications (10,11), thereby playing a role in epigenetic regulation. HMGN1 affects chromatin functions including DNA repair (12) and transcription (13,14); however, its biological function is not fully understood.…”
Section: Hmgn1mentioning
confidence: 99%